Qualidade da fluoretação da água de abastecimento público nos municípios da Região Metropolitana da Grande Vitória, Espírito Santo, Brasil - Belotti, Lorrayne (2017)
The aim of this study was to analyse the quality of public supply water fluoretation at seven cities of Vitoria’s Metropolitan Region - Espirito Santo, (RMGV-ES), Brazil. A descriptive and analytic study was performed by three times. Firstly a critic review included works at Portuguese and English language, published from 1953 (begining of fluoretation at ES state) to 2015. It involved findings about management documents, searches and information from town hall official pages and the company responsible by public supply water at the studied cities. To analyse the documents and articles were considered: year of data findings, quantity of municipalities included, main subject, authors/institutions; methodology, concentration of ion fluoride analysis and witch concentration was finded. About the information from official pages, the features considered were: year, source, characteristic and main paragraph. At the second part, to concentration of fluoride analysis at public supply water, 648 collect of treated water at Water Treatment Stations that supply more than 80% of population from each RMGV-ES municipality, during the period from May to October 2016. The sample were analysed through Specific Electrode Methods and the outcome were organized according to two criteria for interpretation, following the Health Ministry Ordinance nº635/1975 and the criteria proposed by the Collaborating Center of the Health Ministry in Oral Health Surveillance (CECOL). Also demographic, socioeconomic and health-related variables were selected at each municipality. For analysis of concordance between the interpretation criteria, it performed the test and Kappa. The ratio indicator of samples with adequate fluorine was calculated for both criteria. The indicador according to the CECOL criterion was related to the contextual factors by Spearman Test. In the last step, were searched for fluoride control data produced by the public supply company and by municipal surveillance. Surveillance information was accessed in the Information System for Surveillance of Water Quality for Human Consumption (SISAGUA). Then, the means and standard deviations of the results of the samples collected by the three information sources were calculated for the weekly information. These averages were compared statistically. For the monthly samples, made available by the company and SISAGUA, the IPAA was calculated, according to the CECOL proposal, and statistically tested for differences between proportions. In the critical review, five scientific texts were found, as well as information based on management reports, available from the CECOL of the University of São Paulo. Information on company websites and prefectures was superficial. Control and heterocontrol data were not found. The proportion of adequate samples was 68.1% and 81.4% according to the different criteria. The percentage of agreement between the two criteria was 86.69% and presented substantial agreement (Kappa 0,671). The human development index, the supervised toothbrushing and the total population of the municipality showed a strong positive correlation with the ratio indicator of adequate samples. The infant mortality rate and the proportion of extractions exhibited a moderate and negative correlation. The last step of this research showed that the adequacy percentages varied according to the ATS and the months of analysis. The comparison between the percentages exhibited few statistically significant differences (p-value <5%). However, comparisons of the weekly averages among the three sources of information showed statistically significant differences over the six months of follow-up. In addition, it was verified the importance of continuous monitoring of fluoride levels, especially in municipalities with lower social and economic development.